A Comprehensive Physics-Based Equivalent-Circuit Model and State of Charge Estimation for Lithium-Ion Batteries. Issue 9 (24th September 2021) - Pang, Hui; Jin, Jiamin; Wu, Longxing; Zhang, Fengqi; Liu, Kai
Abstract : An accurate battery model plays a vital role in assessing the performance of a lithium-ion battery cell. Although a conventional equivalent circuit model (ECM) such as second-order RC model has been widely employed in developing battery management system, it is difficult to capture the electrochemical behaviors of lithium-ion batteries. To address this issue, we propose a comprehensive physics-based equivalent-circuit model (PECM) and state-of-charge (SOC) estimation method for lithium-ion batteries (LIBs). First, a simplified pseudo two-dimensional model is reformulated in the frequency domain to establish the relationship between the battery electrochemical and electrical properties. Different from the previous methods, the improved boundary conditions of electrolyte are introduced to obtain a group of dynamic electrolyte concentration regarding the variations of electrode thickness. Next, by incorporating the extended Kalman filter, a SOC estimation procedure is presented based on the developed PECM. Finally, the effectiveness of proposed PECM is validated in predicting battery terminal output voltage and SOC in case of two different test profiles. The simulation and experimental results show that, in contrast to the conventional ECM, our developed PECM is more suitable for characterizing the LIBs with high accuracy no matter under the US06 or HPPC current working conditions.